Effectiveness of combined neurometabolic therapy in complex treatment of patients with hemorrhagic hemispheric stroke in recovery period - Dronova, A. O.; Дронова, Анастасія Олександрівна (My University, 2021)
Objective. The aim of this work was to estimate the effectiveness of combination neurometabolic therapy that includes 5 mg of ipidacrine hydrochloride and 300 mg of phenibut in complex therapy of patients with hemisphere hemorrhagic stroke in the early rehabilitation period. Material and methods. Open comparative randomized study and treatment of 46 patients (31 men and 15 women) with hemisphere hemorrhagic stroke in the early rehabilitation period was performed. The mean age of patients was 57.17 ±7.09 years. All patients were divided into two groups - the main group included 20 patients with hemorrhagic stroke, who took neurometabolic combination therapy (5 mg of ipidacrine hydrochloride and 300 mg of phenibut three times per day) in addition to complex recovery treatment during 30 days (start from 30th day after stroke) and control group, that included 26 patients with hemorrhagic stroke, who received standard complex recovery treatment without additional neurometabolic therapy. Outcomes. The median MoCA score of the main group of patients was 21.0 (19; 24), while the second group had 20.5 (18; 23.75) MoCA score, but without any intergroup difference. It was also identified reliable improvement of cognitive values on the MoCA scale after treatment (р ˂ 0.05). Besides, statistical difference was reached between groups in these measures. Also, we showed that statistical improvement in memory was observed in both groups at 1st and 2nd attempts using Luriya’s method “memorizing 10 words”. But subsequent such an effect took place only in the main group. The present study showed the absence of improvement “memorizing of 10 words” at 3rd, 4th and 5th attempts in control group. At the same time, patients of the main group had improved results at 4th and 5th ones (р ˂ 0.05). Conclusion. The combined drug of neurometabolic nature, consisting of 5 mg ipidacrinum and phenibut 300 mg, improved rehabilitation effectiveness rates for account of cognitive functions in patients with hemorrhagic hemispheric stroke during recovery period during comprehensive rehabilitation.
Keywords: hemorrhage stroke; recovery period; rehabilitation; neurometabolic therapy